Confirmation of Brain Death with Positron Emission Tomography - Ozdemir, Semra; Tan, Yusuf Ziya; Ozturk, Fulya Koc; Battal, Fatih (Journal of Pediatric Intensive Care, 2020)
After recent advances regarding organ transplantation, accurate and timely diagnosis of brain death has gained importance. In the diagnosis of brain death, in addition to clinical findings, various ancillary tests are very crucial. In this study, the scintigraphic imaging of the brain death of an 8-year-old girl with both Tc-99m diethylenetriaminepentaacetic and 18F-fluorodeoxyglucose (FDG) has been presented. This case study shows that 18F-FDG positron emission tomography-computed tomography imaging can be a useful technique in evaluating brain death in patients.
Keywords: brain death; diethylenetriaminepentaacetic acid; F-18 fluorodeoxyglucose